2014
DOI: 10.1109/tmi.2014.2313000
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Generation of Myocardial Blood–Oxygen-Level-Dependent MRI Time Series Via Structural Sparse Decomposition Modeling

Abstract: This paper aims to identify approaches that generate appropriate synthetic data (computer generated) for Cardiac Phase-resolved Blood-Oxygen-Level-Dependent (CP–BOLD) MRI. CP–BOLD MRI is a new contrast agent- and stress-free approach for examining changes in myocardial oxygenation in response to coronary artery disease. However, since signal intensity changes are subtle, rapid visualization is not possible with the naked eye. Quantifying and visualizing the extent of disease relies on myocardial segmentation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…To this end, we envision that it would be advantageous to use all images from the CP–BOLD image sequence for a better identification of ischemic regions. Recent experiments on properly generated synthetic data [6] have shown that an independent component analysis (ICA) approach adopted from fMRI [7] outperformed S/D. However, ICA cannot accommodate time shifts present in BOLD time series, which are likely due to physiological differences between different myocardial territories [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, we envision that it would be advantageous to use all images from the CP–BOLD image sequence for a better identification of ischemic regions. Recent experiments on properly generated synthetic data [6] have shown that an independent component analysis (ICA) approach adopted from fMRI [7] outperformed S/D. However, ICA cannot accommodate time shifts present in BOLD time series, which are likely due to physiological differences between different myocardial territories [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, ICA cannot accommodate time shifts present in BOLD time series, which are likely due to physiological differences between different myocardial territories [8]. This shifting in time characteristic CP–BOLD effect , was suspected by Tsaftaris et al [3] and was statistically shown by Rusu et al [6], using a circulant dictionary model.…”
Section: Introductionmentioning
confidence: 99%
“…In disease this effect is not present. However, visualizing and quantifying such patterns requires significant post-processing, including myocardial registration to establish pixel-precise time series for identifying such patterns [12]. Such spatio-temporal intensity variations of the myocardial BOLD effect cause the methods developed for standard CINE MR registration to under-perform.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, no CP-BOLD MR myocardial registration algorithms exist and due to this absence either segmental information [11] or synthetic data sets are used [12], to obtain pixel-wise time series. We assume that it is due to lack of proper similarity criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Fully supervised myocardial segmentation (i.e., separating myocardium from the rest of the anatomy) developed for standard CINE MR, however, underperform in the case of CP-BOLD MR due to the spatio-temporal intensity variations of the myocardial BOLD effect [14,19]. Thus, in addition to violating shape invariance (as with standard CINE MR), the principal assumption of appearance invariance (consistent intensity [12]) is violated in CP-BOLD MR as well.…”
Section: Introductionmentioning
confidence: 99%